Kepuasan Konsumen-dalam-Memediasi-Pengaruh-Kualitas Produk-dan-Persepsi-Harga terhadap-Loyalitas-Pelanggan (Studi pada Jasa Instalasi Mekanik dan Elektronik PT Langgeng Utama Rekaindo Kediri) - Mega Tri Arsita; Zaenul Muttaqien; Diana Ambarwati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The reason of this study is to research the impact of product pleasant and price notion on client loyalty at PT Langgeng Utama Rekaindo Kediri using customer pleasure as a mediating variable. A quantitative technique is used on this take a look at and Structural Equation Modeling-Partial Least Squares (SEM-PLS 4.0) as an evaluation technique. a web questionnaire changed into used to accumulate facts with a 4-point Likert scale and 140 respondents were involved with the purposive sampling technique used. The effects showed that product high-quality shows a advantageous and significant direct impact on client loyalty. rate notion has a high quality effect on client loyalty, but this effect is not statistically significant. Product high-quality shows a high-quality and significant direct effect on client pride. fee perception shows a fantastic and massive direct impact on client satisfaction. client delight has a positive effect on client loyalty, but this effect is not statistically significant. Product high-quality shows a direct impact on client loyalty thru mediation of client pride does now not show tremendous results. The indirect effect of rate belief on client loyalty via mediation of purchaser pride also does not show sizeable consequences.